2013
DOI: 10.2147/vdt.s25513
|View full text |Cite
|
Sign up to set email alerts
|

Current research and clinical trials for a vaccine against Chikungunya virus

Abstract: Chikungunya infection is a self-limiting Aedes mosquito-borne arboviral disease with variable clinical manifestations, ranging from asymptomatic illness to a very severe and crippling arthralgia. Until recently, Chikungunya was a little known disease that re-emerged in 2005-2006, leading to major outbreaks on the Indian Ocean Islands and in South East Asia, and eventually extending its range to temperate regions. It drew global attention due to its explosive onset, extensive geographic distribution, and high m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…Eforts include the development of vaccines of inactivated virus, live atenuated virus (LAV), and virus-like particles (VLPs). In preclinical studies, LAV and VLP vaccines have been promising, but during clinical trials, they have shown inadequate immunogenicity and residual virulence, for example, the risk of production of chronic rheumatism seen for LAV [62]. However, vaccines should be able to induce high levels of neutralizing antibodies, ideally with only one dose, LAV remain good candidates for which atenuation strategies are of central importance.…”
Section: Chikungunya Fevermentioning
confidence: 99%
“…Eforts include the development of vaccines of inactivated virus, live atenuated virus (LAV), and virus-like particles (VLPs). In preclinical studies, LAV and VLP vaccines have been promising, but during clinical trials, they have shown inadequate immunogenicity and residual virulence, for example, the risk of production of chronic rheumatism seen for LAV [62]. However, vaccines should be able to induce high levels of neutralizing antibodies, ideally with only one dose, LAV remain good candidates for which atenuation strategies are of central importance.…”
Section: Chikungunya Fevermentioning
confidence: 99%